Apolipoprotein E polymorphisms are associated with ischemic stroke susceptibility in a Northwest China Han population. Issue 6 (29th November 2017) - Zhao, Li-li; Su, Gang; Chen, Li-xia; Yan, Qi; Wang, Xue-ping; Yuan, Wei; Wang, Lei; Zhang, Zhen-chang
Abstract : Ischemic stroke (IS), the leading neurology cause of death and disability worldwide, is influenced by gene polymorphisms. To explore the association between IS and Apolipoprotein E ( APOE ) gene polymorphisms, a case–control study containing 513 IS patients and 514 controls without IS was conducted in a Northwest China Han population. MassARRAY iPLEX system was applied to determine the APOE polymorphisms according to the alleles of two single nucleotide polymorphisms (SNPs) of APOE, rs429358, and rs7412. The results showed that rs429358 and rs7412 were in Hardy–Weinberg equilibrium (HWE) in both cases and controls groups. APOE ε4 allele, ε4/ε4 genotype, and ε4-containing genotypes were associated with IS. According to the results of Trial of ORG 10172 in Acute Stroke Treatment (TOAST) classification system, APOE ε2 allele, ε4 allele, and ε4/ε4 genotype were associated with large artery atherosclerosis IS subtypes. In addition, the results also indicated that the ε4 allele related to undetermined IS and ε4/ε4 genotype was related to small vessel disease IS. Compared with subjects with non-ε4-containing genotypes, the total cholesterol (TC) and low-density lipoprotein (LDL) level in blood and the proportion of cardiopath history were higher in all subjects with ε4-containing genotypes. Besides, the triacylglycerides (TG) level in blood was higher in controls with ε4-containing genotypes. In conclusion, in a Northwest China Han population, APOE ε4 allele was associated with blood lipid level. The TC and LDL levels were the independent risk factors for IS. APOE was a risk gene for IS, but not independent, especially for large artery atherosclerosis IS.